2022
DOI: 10.1155/2022/3567816
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Prestressed Anchor Cables Supporting Deep Foundation Pit of a Subway Station during Spring Thaw

Abstract: Based on the deep foundation pit for a subway station in Changchun (China), a 3D numerical model of water–heat coupling in a prestressed pile anchor system was established to determine its performance in freezing and thawing seasons in alpine areas. Its reliability was confirmed using field monitoring data on the prestressed anchor cables, which demonstrated changes in surface subsidence, anchor cable axial force, and pile horizontal displacement during spring thaw. The results demonstrated different degrees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Based on the measured data, a general apparent earth pressure envelope of earth pressure was proposed, as was an optimization scheme of diaphragm wall construction and design. Feng et al [20] proved that changes in surface settlement, the axial force of anchor cables, and the horizontal displacement of piles during the spring thawing process can provide a certain reference for the engineering of deep foundation pits in high-altitude and cold regions. Wang et al [21] believes that changes in the water level have a significant impact on the stability of the foundation pit, and has analyzed and optimized the grouting reinforcement parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the measured data, a general apparent earth pressure envelope of earth pressure was proposed, as was an optimization scheme of diaphragm wall construction and design. Feng et al [20] proved that changes in surface settlement, the axial force of anchor cables, and the horizontal displacement of piles during the spring thawing process can provide a certain reference for the engineering of deep foundation pits in high-altitude and cold regions. Wang et al [21] believes that changes in the water level have a significant impact on the stability of the foundation pit, and has analyzed and optimized the grouting reinforcement parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Dong and Yu proposed a numerical model to simulate the frost heave and stress of water pipes and performed experiments to confirm the reliability of the model at simulating the temperature distribution and volume variation [14]. Chou et al, Zhao et al, Han et al, and Feng et al used the software Geo-Studio and demonstrated that the thawing depth of slopes subjected to freeze thaw cycles increased with the freezing depth and that a closed loop isotherm formed on the slope [15][16][17][18][19]. Other researchers have used onsite monitoring, indoor freeze thaw tests, thermal parameter tests, and numerical simulations to examine embankments, cut slopes, rock masses, and tunnels in cold regions [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%